Transcriptional states and chromatin accessibility during bovine myoblasts proliferation and myogenic differentiation. Issue 5 (1st April 2022) - Li, Qian; Wang, Yahui; Hu, Xin; Zhang, Yapeng; Li, Hongwei; Zhang, Qi; Cai, Wentao; Wang, Zezhao; Zhu, Bo; Xu, Lingyang; Gao, Xue; Chen, Yan; et al.
Abstract: Objectives: Although major advances have been made in bovine epigenome study, the epigenetic basis for fetal skeletal muscle development still remains poorly understood. The aim is to recapitulated the time course of fetal skeletal muscle development in vitro, and explore the dynamic changes of chromatin accessibility and gene expression during bovine myoblasts proliferation and differentiation. Methods: PDGFR‐ cells were isolated from bovine fetal skeletal muscle, then cultured and induced myogenic differentiation in vitro in a time‐course study (P, D0, D2, and D4). The assay for transposase‐accessible chromatin sequencing (ATAC‐seq) and RNA sequencing (RNA‐seq) were performed. Results: Among the enriched transcriptional factors with high variability, we determined the effects of MAFF, ZNF384, and KLF6 in myogenesis using RNA interference (RNAi). In addition, we identified both stage‐specific genes and chromatin accessibility regions to reveal the sequential order of gene expression, transcriptional regulatory, and signal pathways involved in bovine skeletal muscle development. Further investigation integrating chromatin accessibility and transcriptome data was conducted to explore cis‐regulatory regions in line with gene expression. Moreover, we combined bovine GWAS results of growth traits with regulatory regions defined by chromatin accessibility, providing a suggestive means for a more precise annotation of genetic variants of bovine growth traits. Conclusion: Overall, these findings provide valuable information for understanding the stepwise regulatory mechanisms in skeletal muscle development and conducting beef cattle genetic improvement programs. Abstract : Here, we conducted ATAC‐seq and RNA‐seq to profile chromatin accessibility and gene expression dynamics over a time course spanning from bovine foetal myoblasts proliferation and myogenic differentiation. Additionally, we integrated our data with results from genome‐wide association study (GWAS) of bovine growth traits to characterize the functions of these regulatory elements. Taken together, our study demonstrated a step‐wise dissection of the transcriptional regulation network for skeletal muscle development and provide a systematic understanding of the molecular circuits governing skeletal muscle development.